Keefektifan Pengukuran Kebutuhan Belajar Menggunakan Model Deduktif di Masa Pandemi Covid-19 di SDN Serdang Wetan - A’la, Nadia Ibadatul; Bilqist, Philien Sophia Ikrima; Aini, Vika Zahra (ANWARUL, 2022)
In learning activities, a teacher must understand what is needed by students. In identifying student learning needs, an appropriate learning needs measurement model is needed. One of them is the inductive model. The deductive model is the identification of learning needs in general and with broad targets. The effectiveness of the deductive model was tested by research sourced from the results of an interview with an elementary school teacher. The deductive model is often applied in a learning model. This is useful to find out how effective the learning model has been. The deductive model that conveys messages from the general to the specific and the abstract to the real turns out to have advantages and disadvantages when applied online.